Pendeteksian Potensi Kecurangan Pelaporan Keuangan dengan Beneish Model (Studi pada Perusahaan Badan Usaha Milik Negara yang Terdaftar di BEI) - Rahman, Rizqa Awalia (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2019)
As the world is becoming more globalized than before, financial market participants especially in Indonesia face serious risk for dealing with fraudulent financial reporting. This study aims to detect potential fraud reporting by using Beneish M-Score Model. Sample in this studi is Indonesia State Owned Enterprises who listed in Indonesia Stock Exchange from 2016 to 2018. Our evidence conclude that Beneish Model supports effectively in analyzing characteristics of falsified financial statements.